2021
DOI: 10.1089/whr.2020.0116
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment, Decision-Making Preferences, and Interest in Evidence-Based Diabetes Prevention among Women with a History of Gestational Diabetes Mellitus

Abstract: Background: The Diabetes Prevention Program (DPP) showed that lifestyle change or metformin is equally efficacious in preventing diabetes in women who have had gestational diabetes mellitus (GDM). Few studies have investigated the relationship between education and willingness to engage in either intervention and between education and preferred decision-making style. Methods: Within a large health system, we surveyed insured women 18–64 years old with a history of GDM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We also had limited opportunity to examine education or income. While important social determinants of health [3], recent research among patients with GDM indicates that interest in behavioral intervention for diabetes prevention did not differ across levels of education [14]. Finally, evaluation respondents were more likely than nonrespondents to have completed more intervention sessions, and therefore may have more positively evaluated the intervention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also had limited opportunity to examine education or income. While important social determinants of health [3], recent research among patients with GDM indicates that interest in behavioral intervention for diabetes prevention did not differ across levels of education [14]. Finally, evaluation respondents were more likely than nonrespondents to have completed more intervention sessions, and therefore may have more positively evaluated the intervention.…”
Section: Discussionmentioning
confidence: 97%
“…For patients with GDM, barriers to participation in postpartum diabetes prevention include time constraints, fatigue, and other demands of parenthood [13]. Yet recent research indicates strong interest in behavioral intervention for diabetes prevention [14], which can be further strengthened via theory-driven strategies [15]. In fact, a history of GDM has been linked with greater engagement in diabetes prevention activities [16].…”
Section: Discussionmentioning
confidence: 99%
“…Howe et al [ 28 ] conducted a within-sibship MR study that revealed a strong association between higher EA and lower BMI. Furthermore, in an observational study, Panchal et al [ 29 ] found that individuals with lower EA (less than college graduates) had higher BMI than those with higher EA (college graduates and post-college degrees) [31.8 ± 6.4 vs. 29.6 ± 4.8 vs. 29.7 ± 5.2, p = 0.04]. These findings align with our study results, indicating a robust and significant causal association between obesity-related traits, such as BMI, BF%, WHR (indicative of central obesity), and the incidence of GDM.…”
Section: Discussionmentioning
confidence: 99%